Dynamic methods of air traffic flow management - Jacek SKORUPSKI (Transport Problems, 2011)
Air traffic management is a complex hierarchical system. Hierarchy levels can be defined according to decision making time horizon or to analyze area volume. For medium time horizon and wide analysis area, the air traffic flow management services were established. Their main task is to properly co-ordinate air traffic in European airspace, so as to minimize delays arising in congested sectors. Those services have to assure high safety level at the same time. Thus it is a very complex task, with many goals, many decision variables and many constraints.In the paper review of the methods developed for aiding air traffic flow management services is presented. More detailed description of a dynamic method is given. This method is based on stochastic capacity and scenario analysis. Some problems in utilization of presented methods are also pointed out, so are the next research possibilities.